KECERDASAN INTRAPERSONAL GURU PAUD SE-KECAMATAN KAMPAR KIRI HILIR KABUPATEN KAMPAR - Rinda Agustine Rinda Agustine; Wusono Indarto Wusono Indarto; Enda Puspitasari Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this study aims to determine intrapersonal intelligence early childhoodteachers in the districts kampar kiri hilir of kampar regency. As for the population ansample is whole early childhood teacher totaling 30. Data collection techniques wereused that test in the form guttman scale. Data analysis techniques using percentage. Ofthe result intrapersonal intelligence early childhood teachers in the district kampar kirihilir of kampar regency overall percentage of 60% was high category. Whereas, ifviewed from each of brackish indicators, , high self assessment indicator percentage of68,33% in the high category, in the moderate category self relient attitude indicator haspercentage of 65% in the high category,indicator of self knowledge about the goalsthemselves percentage of 60,83% in the high category, indicator of skill of express,thoughts, feelings, opinions and beliefs percentage of 46,66%, , indicator of selfknowledge will be of personal valves percentage 43,33% in the moderate category.Keywords: Intrapersonal Intelligence